Key Factors for Achieving Green Competitive Advantage through the Mediation of Green Innovation in Addressing Environmental Concerns - Hadi, Jonathan Edward Surya; Indudewi, Febe Yuanita Ratna (Jurnal Entrepreneur dan Entrepreneurship, 2025)
Environmental degradation has significantly intensified, raising global concerns, particularly in Indonesia. This issue impacts micro-businesses as consumers become increasingly environmentally conscious, especially in Surabaya. In response, businesses are adopting green innovations to meet market demands and gain a competitive advantage in sustainability. This study aims to identify the key factors for achieving a green competitive advantage through green innovations, which mediate the relationship between external environmental orientation and green dynamic capabilities. The method of this study is a quantitative methodology, utilizing a 6-point Likert scale online questionnaire for data collection. The sample comprises 142 green micro-businesses in the Surabaya region, selected using purposive sampling. Data are analyzed using SmartPLS software. The results indicate significant direct relationships between external environmental orientation, green dynamic capabilities, and green competitive advantage. Additionally, external environmental orientation and green dynamic capabilities significantly influence green innovation. The results also highlight indirect relationships between the independent variables and green competitive advantage, with green innovation partially mediating the proposed model.